AUTOMOTIVE TRANSPORT AND PROBLEM OF TRAFFIC SAFETY IMPROVEMENT - A. V. Bessarab (Наука и техника)
Provision and improvement of safety in respect of operated automotive and transport facilities is of great significance all over the world. This problem is rather actual for automotive transport in the Republic of Belarus.An analysis of absolute and relative accident indices, operated automotive fleet, number of road traffic accidents caused by technical failure has been carried out on the basis of the results pertaining to operation of transport facilities in the Republic in 2011. The paper considers a role of technical state of road transport vehicles as a reason of transport accidents